Plantas acuáticas de las planicies inundables de la Orinoquia colombiana (2016)
The vast floodplains of the Orinoco Basin have the conditions for the proliferation of aquatic vegetation. Despite its ecological importance in the “Llanos Orientales” of Colombia, the aquatic flora in this region has been understudied. Consequently, the knowledge and dissemination of information about the richness and distribution patterns of aquatic plants and aquatic communities is scarce. In addition, the Orinoco Basin of Colombia is among the most over-exploited regions in the country. In order to provide a first insight into the species richness of macrophytes present in the region, plants associated with aquatic habitats were collected, identified, and photographed. For almost two years, 101 localities were visited. These localities were located in six departments (Arauca, Casanare, Guainía, Guaviare, Meta and Vichada) and 19 municipalities. In each locality, dried plant material and silica-dried material were collected. Sampling effort was concentrated towards hydrophytes and helophytes inhabiting lentic and lotic environments. 1167 collected specimens were deposited in the ANDES herbarium (Universidad de los Andes, Bogotá). Among these, 95 families, 221 genera, and 341 species of vascular plants were associated with aquatic habitats. Of the species collected, only 151 had been reported in the study area with 1374 historic occurrences in the “Herbario Nacional Colombiano” (COL) database. The present study aims to contribute to the knowledge and dissemination of information about the richness and distribution patterns of macrophytes in the Orinoco Basin of Colombia. We consider that this information is important in order to propose localities that should be a priority for conservation purposes, and to protect these important and threatened fresh-water ecosystems.